An in vitro assay to study the recruitment and substrate specificity of chromatin modifying enzymes - Vermeulen, Michiel (Biological Procedures Online, 2004)
Post-translational modifications of core histones play an important role in regulating fundamental biological processes such as DNA repair, transcription and replication. In this paper, we describe a novel assay that allows sequential targeting of distinct histone modifying enzymes to immobilized nucleosomal templates using recombinant chimeric targeting molecules. The assay can be used to study the histone substrate specificity of chromatin modifying enzymes as well as whether and how certain enzymes affect each other's histone modifying activities. As such the assay can help to understand how a certain histone code is established and interpreted.